Early functional mismatch between breast cancer cells and their tumour microenvironment suppresses long term growth. (28th September 2022) - Perdrix Rosell, Anna; Maiques, Oscar; Martin, Joshua Alexander James; Chakravarty, Probir; Ombrato, Luigi; Sanz-Moreno, Victoria; Malanchi, Ilaria
Abstract: Cancer cells thrive when embedded in a fine-tuned cellular and extracellular environment or tumour microenvironment (TME). There is a general understanding of a co-evolution between cancer cells and their surrounding TME, pointing at a functional connection between cancer cells characteristics and the perturbations induced in their surrounding tissue. However, it has never been formally proven whether this functional connection needs to be set from the start or if aggressive cancer cells always dominate their microenvironmental any point in time. This would require a dedicated experimental setting where malignant cells are challenged to grow in a different TME from the one they would naturally create. Here we generated an experimental setting where we transiently perturb the secretory profile of aggressive breast cancer cells without affecting their intrinsic growth ability, which led to the initial establishment of an atypical TME. Interestingly, even if initially tumours are formed, this atypical TME evolves to impair long term in vivo cancer growth. Using a combination of in vivo transcriptomics, protein arrays and in vitro co-cultures, we found that the atypical TME culminates in the infiltration of macrophages with STAT1 high activity. These macrophages show strong anti -tumoural functions which reduce long-term tumour growth, despite lacking canonical M1 markers. Importantly, gene signatures of the mesenchymal compartment of the TME, as well as the anti -tumoural macrophages, show striking prognostic power that correlates with less aggressive human breast cancers. Highlights: Uncoupling breast cancer cell intrinsic potential from TME activation results in impaired tumour growth. Long term impairment of growth is due to early differences in tumour microenvironment. Fibroblasts and non-canonical macrophages are crucial for limiting tumour growth. We define a specific tumour microenvironment with strong prognostic features for breast cancer patients.